Case report: Azithromycin-meropenem combination therapy as a low-cost approach to combat PDR gram-negative infections of war wounds in Ukraine - Kryzhevskyi, Vadym; Strokous, Viktor; Lifshyts, Yurii; Rybianets, Yurii; Oberniak, Artem; Krikunov, Alexey; Iungin, Olga; Potochilova, Viktoria; Rudnieva, Kateryna; Petakh, Pavlo; Kamyshnyi, Aleksandr; Moshynets, Olena (Frontiers in Medicine, 2023)
Antimicrobial resistance recognised as a major global health problem and it poses a significant challenge in conflict zones, such as the Russia-Ukraine war. This case study focuses on a 32-year-old soldier who sustained combat-related injuries, including extensive wound infections caused by multidrug-resistant and pan-resistant bacteria and was successfully treated with azithromycin-meropenem combination therapy. The emergence of pan-resistant bacteria, particularly a pandrug-resistant strain of Pseudomonas aeruginosa, highlights the severity of the problem and the limited treatment options available. Additionally, the financial burden posed by reserve antibiotics further complicates the management of these infections. The case study demonstrates the effectiveness of including azithromycin-meropenem combination therapy in the treatment regimen, which resulted in improvements in the patient’s condition and the eradication of the resistant strains. The findings underscore the need for effective antimicrobial stewardship, infection control measures, and alternative treatment strategies to combat antimicrobial resistance in conflict zones.